Menuju generasi emas: Pendidikan sebagai jembatan menuju masa depan - Hanifah, Huriyyatusy Syauqiy (Maliki Interdisciplinary Journal, 2024)
Indonesia has a big dream, namely, to create a great generation that is ready to compete in 2045, which we call the "Golden Generation". This generation is expected to be able to bring Indonesia forward rapidly. To realize this dream, education is very important, like a bridge to a bright future, how quality education can be a strong foundation for the Golden Generation. We need several important things that need to be fixed, the first is, All Children Have the Right to Learn. Every child, wherever they live, must have the same opportunity to learn. So, this problem is serious to overcome the differences in learning opportunities in cities and villages. Second, Learning According to the Times The curriculum must be designed so that children learn what is needed in the future. The curriculum must follow technological developments, the needs of the world of work, and global challenges. This is important so that children can adapt and be innovative. Third, Good Character The Golden Generation is not only smart, but also has good character. Values ​​such as honesty, responsibility, and tolerance must be taught from an early age. And finally, Cooperation for Success: The government, schools, and society must work together to build a good education system. All parties must actively improve the quality of education, build learning facilities, and provide sufficient resources. In essence, education is a long-term investment that is very important to achieve Indonesia’s dream of becoming a "Golden Generation". By increasing access to learning, creating a relevant curriculum, building character, and working together, Indonesia can produce a young generation that is ready to face the future and lead this nation towards better progress.